Cyclic cracking resistance of brittle materials in compressive loading - Lanin, A.G. (Проблемы прочности, 2009)
Fatigue behavior of brittle materials under compression is considered. The findings should be taken into account in the failure probability assessment of components made of materials with limited plasticity, which are used in various stress states.